OUTBACK PARTS OF SOCIAL ARRANGEMENT BEING RITUAL ART STAGE IN THE MALAY PELALAWAN RIAU - Nursyirwan Nursyirwan; Delfi Enida (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2019)
This research globally examines sounds and deals with the fact that inland tribes functioned in medical rituals that were transformed into stage art entertainment. Certain sounds and movements by the Inland Tribe in medicine have meaning and importance. Why the sounds were functioned in a medical ritual which was later changed the function of medicine in the interior to stage art. How is the interaction and form in the ritual of treatment that requires sounds. Research wants to give the same social attention to art and culture to the tribal civilization, which is sometimes considered backward. This research answers the social prejudices of the transfer of treatment locations from the interior to the stage art. The research technique / method uses qualitative techniques with studies in ethnomusicology, ethnography, art anthropology and art sociology. In the study found a management system that leads to a new theory of "Performance Art for the transfer of issues regarding the existence of Malay Tribal Culture"; practically building a model of the composition of the art of the Tribal Inland tradition as a consumption of urban communities, in the context of the new art culture in the present. Outcomes Research can conclude the uplift of the Tribal Civilization both in terms of music, other arts and all aspects of art do have values that are worth showing, but on the side or behind it turns out there is a certain mission by parties related to arts and culture in the study area Malay.